(untitled) (Revista de História Regional, 2007)
In this article, we intend to prove that the Andean witchcraft is the result of a confluence of cultural speeches. In the current historiography, begin to appear studies that analying the role of signs in the construction of a cultural history. Working with the chronicles of XVI and XVII centuries, we verified that there are different speeches regarding indigenous structures, and that sometimes, they were modified to assist to the colonial needs. Our concern is to approach the chronicles as the output of a semiosis.